2020
DOI: 10.1007/s00392-020-01661-6
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of the novel CMR parameter “myocardial transit-time” (MyoTT) for the assessment of microvascular changes in cardiac amyloidosis and hypertrophic cardiomyopathy

Abstract: Background Coronary microvascular dysfunction (CMD) is present in various non-ischemic cardiomyopathies and in particular in those with left-ventricular hypertrophy. This study evaluated the diagnostic value of the novel cardiovascular magnetic resonance (CMR) parameter “myocardial transit-time” (MyoTT) in distinguishing cardiac amyloidosis from other hypertrophic cardiomyopathies. Methods N = 20 patients with biopsy-proven cardiac amyloidosis (CA), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Previous studies reported a high prevalence of coronary microvascular dysfunction in cardiac amyloidosis in the absence of epicardial coronary artery disease and in comparison with hypertrophic cardiomyopathy 3,14 . In this study, we directly assessed CD from cardiac tissue and comprehensively described structural and functional cardiac abnormalities associated with process of capillary rarefaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported a high prevalence of coronary microvascular dysfunction in cardiac amyloidosis in the absence of epicardial coronary artery disease and in comparison with hypertrophic cardiomyopathy 3,14 . In this study, we directly assessed CD from cardiac tissue and comprehensively described structural and functional cardiac abnormalities associated with process of capillary rarefaction.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported a high prevalence of coronary microvascular dysfunction in cardiac amyloidosis in the absence of epicardial coronary artery disease and in comparison with hypertrophic cardiomyopathy. 3 , 14 In this study, we directly assessed CD from cardiac tissue and comprehensively described structural and functional cardiac abnormalities associated with process of capillary rarefaction. These findings of our study provide mechanistic insight into the pathological process of capillary rarefaction with infiltration of amyloid and underscore capillary rarefaction as a probable mechanism for diastolic dysfunction and [LV GLS] impairment in cardiac AL amyloidosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in the diagnosis of microvascular diseases, Chatzantonis et al ( 66 , 67 ) introduced a new cardiovascular magnetic resonance (CMVD) parameter named “myocardial transit-time” (MyoTT), which is defined as the blood circulation time from the orfice of the coronary artery to the collection of the coronary sinus. MyoTT reflects the transmission time of gadolinium in myocardial microvascular.…”
Section: Research Progress Of Imaging Methods For Detection Of Microvascular Angina Pectorismentioning
confidence: 99%
“…Heart failure with preserved ejection fraction (HFpEF) is a common manifestation of CA patients, and ultimately progress to heart failure with reduced ejection fraction (HFrEF). Chest pain symptom may present in a proportion of CA patients without significant coronary arteries stenosis (<50%) by angiography, and the microcirculation impairment of CA patients was previously reported (13)(14)(15)(16). In severe cases, it can lead to filling defect on first-pass perfusion images (17,18).…”
Section: Introductionmentioning
confidence: 93%